Treatment of a full-thickness skin lesion in a prematurely born infant. Integra® Bilayer for bridging to skin grafting until epidermal maturation allows safe harvesting. A rare case. Issue 3 (July 2021) - Mueller-Eggenberger, Michel; Kanduth, Claudia; Rab, Matthias; Breschan, Christian; Neuwirth, Maximilian
Highlights: Skin maturation in very early born infants is ongoing post-partum, considerations for skin harvesting in these patients. Successful use of a dermal substitute in a preterm born neonate. Prolonged application of dermal substitute with a superficial silicon layer seems safe. Abstract: We report a case of a highly premature born infant in the 24th week of gestation that suffered from an extravasation injury. A central venous catheter caused a large full-thickness defect at the chest. Coverage was necessary and provided by using a split skin graft; however, at this age dermal maturation is not completed and the skin is much thinner and less functional in terms of mechanical strength and epidermal layering. When harvesting skin, this may result in secondary defects. The authors describe the successful and novel use of a dermal substitute with a superficial silicon layer (Integra® Bilayer) to bridge the time until neonatal skin development allows safe skin harvesting. A positive side effect is that the use of this dermal substitute also improved the scar quality in the premature infant.